Ruptured tubal pregnancy in an undiagnosed heterotopic pregnancy - Juneja, Sunil K.; Tandon, Pooja; Kochhar, Bakul; Narang, Monika; Badan, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Heterotopic pregnancy is rare obstetrical emergency the diagnosis of which is usually delayed. A high degree of suspicion is required to diagnose to reduce maternal morbidity and mortality. At the same time salvage of the intrauterine pregnancy can be done.